Analysis of stresses in drilled composite materials - Fernandes, M.G.A. (2015)
In this study, a three-dimensional dynamic model was built to simulate the drilling process in the composite materials. With an explicit dynamic simulation it is possible to obtain large structural deformation and to apply high intensity loading in a short time frame. Using this methodology, the influence of different cutting parameters were considered during the drilling process in typical composite materials. Also, similar tests were produced in laboratory using composite blocks. Each composite material was instrumented with strain gauges to obtain the strain in different surface positions during the drilling process. The results from the numerical methodology were compared with the experimental methodology. It was concluded when the feed-rate is higher the stresses and strains in the composite material are lower. The obtained numerical and experimental results were similar. Therefore the developed numerical model proved to be a great tool in this kind of analysis.